2022
DOI: 10.7150/jca.61437
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA_400029 promotes the aggressive behaviors of cervical cancer by regulation of miR-1285-3p/TLN1 axis

Abstract: Background: Cervical cancer (CC) is the highest incidence of female malignant tumor in China. Circular RNAs (circRNAs) has been reported to affect CC progression by altering mRNA stability at the transcriptional level or binding to miRNAs to produce competitive endogenous RNA (ceRNA). For this purpose, our study was aimed to investigate the function effects and the potential regulatory mechanism of the circRNA_400029 in CC cells. Materials and methods:The expression levels of circRNA_400029 and miR-1285-3p wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…ITGB1, a crucial integrin subunit, is essential for mediating cell-ECM interactions, thereby contributing to the formation of focal adhesions ( 71 ). Furthermore, various other proteins present in EVs, such as ANXA2 ( 72 , 73 ), TLN1 ( 74 ), ENO1 ( 75 ), and TFRC ( 76 ) exhibit substantial overexpression in cervical cancer. These proteins play a role in cell adhesion and movement, regulating tumor cell proliferation and metastasis, and are also linked to patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…ITGB1, a crucial integrin subunit, is essential for mediating cell-ECM interactions, thereby contributing to the formation of focal adhesions ( 71 ). Furthermore, various other proteins present in EVs, such as ANXA2 ( 72 , 73 ), TLN1 ( 74 ), ENO1 ( 75 ), and TFRC ( 76 ) exhibit substantial overexpression in cervical cancer. These proteins play a role in cell adhesion and movement, regulating tumor cell proliferation and metastasis, and are also linked to patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circRNA_400029 promoted cervical cancer progression by sponging miR‐1285‐3p, finally regulating TLN1 expression. 35 Moreover, circRNAs can interact with RBPs. Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circRNA_400029 promoted cervical cancer progression by sponging miR-1285-3p, finally regulating TLN1 expression. 35 Moreover, circRNAs can interact with RBPs. Zhang et al 11 showed that circVPS13C could bind with RRBP1 proteins to decrease the stability of IFITM1 mRNA, eventually promoting pituitary adenoma progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The competitive endogenous RNA (ceRNA) theory, which proposes that non-coding RNA, mRNA, and other transcripts can competitively bind miRNA response elements (MREs) to mutually regulate the expression of their respective genes, is central to the interaction mechanism between RNAs [6]. A large number of studies have discovered that aberrant circRNA regulation causes a variety of diseases, including cervical cancer [7][8][9]. Through bioinformatics research and multiple databases, such as the Gene Expression Omnibus (GEO) database, the cancerspeci c circRNA database (CSCD), and the TargetScan database, we attempt to create the circRNA-miRNA-mRNA-related ceRNA regulation network for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%